Exploring the Role of Complementary Herbal Therapies (Red Ginger, Aloe Vera, Tangerang Turmeric, Cinnamon, Binahong Leaves, Green Betel Leaves) in Science Education: A Case Study on the Healing Process of Second-Degree Perineal Wounds in Postpartum Mothers - Lili Farlikhatun; Anisaul Husna; Berliana Puji Restuti; Iin Munarti; Kurniasih Anisa Putri; Rif’ah Mutiah; Sundari Sundari (Jurnal Penelitian Pendidikan IPA, 2025)
Regular perineal care is needed to maintain skin integrity and prevent infection, pharmacological treatment has begun to be avoided because the use of antibiotics in postpartum mothers in certain amounts must be limited, so switching to natural therapies such as red ginger, aloe vera, tamarind turmeric, wood sweet, binahong leaves and green betel leaves. This research to determine the effectiveness of complementary therapies (red ginger, aloe vera, tamarind turmeric, cinnamon, binahong leaves, green betel leaves) on the length of healing of perineal wounds in postpartum mothers. Design method this research is quasi experimental with a two group pretest-posttest design. The samples in this study were all postpartum mothers who experienced grade II perineal wounds at PMB Mirah, PMB Sri Poniati, PMB Anita, PMB C, and PMB Indah Meilysa Manik in November 2024 - January 2025 totaling 182 people, the sampling technique was total sampling. The result is complementary therapy is effective in healing perineal wounds, with P-Value of red ginger (0.00), aloe vera leaves (0.00), tamarind turmeric (0.00), cinnamon (0.01), binahong leaves (0.00), green betel leaf (0.03). Complementary therapy (red ginger, aloe vera leaves, tamarind turmeric, cinnamon, binahong leaves, green betel leaves) is effective in healing perineal wounds in postpartum women (P-Value <0.05). It is hoped that midwives can introduce complementary therapies for treating perineal wounds and become a reference in educational institutions.